ANALYSIS OF THE JUDGE'S LEGAL CONSIDERATIONS ON THE TRADEMARK DISPUTE BETWEEN HONGYUNHONGHE TOBACCO (GROUP)Co. Ltd AND PT SUMATRA TOBACCO TRADING COMPANY (STUDY OF SUPREME COURT DECISION NUMBER 76 K/Pdt.Sus-HKI/2024) - Firman Simarmata; OK. Saidin; Rosnidar Sembiring (PT. Radja Intercontinental Publishing, 2024)
This study examines the legal considerations of the judges in resolving trademark disputes between Hongyunhonghe Tobacco (Group) Co. Ltd and PT Sumatra Tobacco Trading Company. The focus lies on the Supreme Court decision Number 76 K/Pdt.Sus-HKI/2024, which serves as a significant precedent in intellectual property rights law in Indonesia. The research aims to evaluate the legal protection provided for registered trademarks and analyze the dispute resolution mechanisms implemented in Indonesia, including the rationale behind the Supreme Court's decision. Using a normative legal research method, this study investigates primary and secondary legal sources to draw conclusions. The findings highlight that the proper registration and active use of trademarks are crucial in asserting ownership and protecting market rights. Furthermore, the court's decision reflects a strict application of the Trademark Law (Law Number 20 of 2016), emphasizing fairness for genuine trademark holders. This research contributes to understanding how trademark disputes are handled and offers insights into strengthening legal frameworks for trademark protection in Indonesia.